Piqueteros after the Hype: Unemployed Movements in Argentina, 2008-2015 - Kaese, Fynn; Wolff, Jonas (European Review of Latin American and Caribbean Studies, 2016)
The Argentine unemployed movement of the piqueteros was a key socio-political player in the early 2000s. Although public and academic attention paid to these piqueteros has decreased notably since 2010, they continue to be active. This article provides an empirical update to the existing research on Argentina’s unemployed movement by analysing how distinct piquetero organizations have adapted to evolving political and socioeconomic changes during the presidency of Cristina Fernández de Kirchner (2008-2015). In drawing on social movement research, we suggest a number of mechanisms that can help to explain the continuing existence of the piqueteros. While a persistent focus on grassroots work has been identified as key to their existence, adaptation to the changing political and socioeconomic context has meant that core claims related to the very issue of (un-)employment, including the demand for dignified work, have largely been dropped from the political agenda of various piquetero organizations. Resumen: Los piqueteros después del auge: Los movimientos de desocupados en Argentina, 2008-2015 A comienzos del siglo el movimiento de desocupados de Argentina era un actor sociopolítico clave, pero desde 2010 ha decrecido notablemente el interés público y académico en los denominados piqueteros. Los piqueteros, sin embargo, siguen existiendo. Este artículo ofrece una actualización de la investigación existente sobre el movimiento de desocupados en Argentina. Se analiza cómo las distintas organizaciones piqueteras han adaptado a los cambios politicos y socioeconómicos durante la presidencia de Cristina Fernández de Kirchner (2008-2015). Basándonos en la investigación sobre movimientos sociales, sugerimos una serie de mecanismos que contribuyen a entender la persistencia de los piqueteros. Por un lado, un continuo enfoque en el trabajo territorial ha sido clave para tal persistencia. Por otro, la adaptación al nuevo contexto ha llevado a que reivindicaciones importantes relacionadas justamente al tema del (des-)empleo, como la demanda por un trabajo digno, hayan perdido relevancia en la agenda política de las distintas organizaciones piqueteras.